Greenspace in prison improves well-being irrespective of prison/er characteristics, with particularly beneficial effects for younger and unsentenced prisoners, and in overcrowded prisons - Moran, Dominique (European journal of criminology, 2024)
In this paper, we present evidence of estimated significant associations between greenspace and prisoners? self-reported well-being, self-harm and violence in prisons in England and Wales. Refining and extending our previous research that estimated the relationship between greenspace and self-harm and violence while controlling for the effects of prison characteristics (e.g. prison size, over-crowding and security level), the findings in the present study show that greenspace remains significantly related to self-harm and violence when we additionally control for prison population characteristics (such as prisoner age, ethnicity, sentence length) and when we use additional self-reported indicators of well-being. Furthermore, our findings also show that the beneficial effects of greenspace appear to be particularly prominent in prison establishments that suffer from overcrowding or hold relatively large shares of younger and un-sentenced prisoners. Finally, our results reveal that greenspace has important impacts on the inter-relationships between self-reported well-being, self-harm and prison violence.